PENGARUH MOTIVASI KERJA, KERJASAMA TIM DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPDIT CU PARDOMUAN DOLOK SANGGUL - Simangunsong, Elisabeth; Sianturi, Laonma; Sitanggang, Darna; Haloho, Elizabeth; Purba, Betniar (Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of work motivation, teamwork and work environment on employee performance at KOPDIT CU Pardomuan Dolok Sanggul. The total population is 57 employees and all members of the population are sampled, namely 57 employees. The sampling technique is a census. Data collection was carried out through questionnaires, documentation and interviews. The research method used is descriptive quantitative. From the results of the t test indicate that work motivation, teamwork, and work environment have a positive and significant partial effect on employee performance. The results of the F test show that simultaneously work motivation, teamwork, and work environment have a significant effect on employee performance. From the results of this study obtained multiple linear regression equations; KK= 4.829+ 0.774(X1) + 0.680(X2) + 0.471(X3) + ei. The coefficient of determination is 0.700, meaning that employee performance can be explained by work motivation, teamwork and work environment by 70%, while the other 30% is explained by other variables not included in this study.